ChemInform Abstract: 4, 2′:6′, 4′′‐Terpyridines: Diverging and Diverse Building Blocks in Coordination Polymers and Metallomacrocycles. Issue 27 (8th July 2014) - Housecroft, Catherine E.
Abstract Review: 44 refs.